Digital and Organisational Innovations in Hajj Education: A Documentary Analysis of NAHCON’s Training and Pilgrim Orientation Systems in Nigeria - Rasheed Olalekan Azeez; Nafiu Olamilekan Ayinde (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2025)
This study examines the emerging transformation of Hajj education in Nigeria within the context of digitalisation and organisational reform. The need for this research arises from long-standing challenges associated with fragmented training structures, inconsistent dissemination of information, and limited technological integration in the preparation of Nigerian pilgrims. Although existing studies have explored administrative and logistical dimensions of Hajj management, they have not sufficiently analysed the educational implications of NAHCON’s reforms from the perspective of Islamic Education. The purpose of this research is therefore to investigate how digital innovations and organisational restructuring within the National Hajj Commission of Nigeria (NAHCON) have shaped the design, delivery, and effectiveness of Hajj education. The study adopts a qualitative documentary analysis method, drawing on official guidelines, organisational documents, statutory instruments, and relevant scholarly literature. The findings reveal that NAHCON has developed a more coherent and standardised national system of Hajj education supported by three major developments: the introduction of digital platforms for registration, information management, and communication; the strengthening of organisational structures that coordinate training and orientation; and the emergence of an implicit national curriculum that integrates ritual instruction, health education, safety protocols, logistical preparation, and financial literacy. These developments represent a significant shift from earlier decentralised systems and demonstrate the growing alignment between religious education and technological-organisational innovation. The study concludes that NAHCON’s reforms have enhanced the accessibility, consistency, and professionalism of Hajj education in Nigeria. Its contribution lies in reframing Hajj preparation as an organised educational process, offering new insights for Islamic Education scholarship, Hajj administrators, and policymakers seeking to improve large-scale religious learning systems.